Political Games: Strategy, Persuasion, and Learning - Gratton, Gabriele (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Political actors navigate a world of incomplete and noisy information. Voters make decisions about turnout and voting amidst campaign promises, credit claiming, and fake news. Policymakers experiment with reforms amidst uncertain predictions from experts and biased interest groups. Parties form coalitions and sign agreements amidst cheap talk and strategic communication. Beyond democracies, autocrats and dictators rule under uncertain threats to their regimes. In all of these environments, some political actors have incentives to learn and gather information, while others have incentives to influence and manipulate this information. This Special Issue addresses the question of how information structures, information transmission, and communication technologies influence political environments and affect the incentives faced by political actors. This is a collection of articles, combining game-theoretical and experimental work. The articles promote novel ideas and address understudied questions, which range from salience determination to microtargeting, ambiguous voting and information naivety. The findings complement the existing literature and suggest rationales for inefficiencies that arise in political environments with incomplete and noisy information.